Direct writing of textured ceramics using anisotropic nozzles. Issue 3 (March 2021) - Walton, Rebecca L.; Brova, Michael J.; Watson, Beecher H.; Kupp, Elizabeth R.; Fanton, Mark A.; Meyer, Richard J.; Messing, Gary L.
Abstract: Direct writing is a unique means to align anisotropic particles for the fabrication of textured ceramics by templated grain growth (TGG). We show that alignment of tabular barium titanate (BT) template particles (20–40 μm width and 0.5–2 μm thickness) in a PIN-PMN-PT matrix powder ( d 50  = 280 nm) is significantly improved during direct writing using anisotropic nozzles at high printing rates. The particle orientation distribution in as-printed filaments, and the texture orientation distribution in sintered ceramic filaments are shown to directly correlate with COMSOL Multiphysics-predicted torque distributions for direct writing with aspect ratio 2, 3 and 5 oval nozzles. Electromechanical strain properties of the textured piezoelectric ceramics significantly improved relative to random ceramics when printed with anisotropic nozzles. Simulations of aspect ratio 20 nozzles and nozzles with interior baffles demonstrate significantly increased torque and near elimination of constant shear stress cores (i.e. plug flow).